2009
DOI: 10.1002/uog.6583
|View full text |Cite
|
Sign up to set email alerts
|

OC22.04: The importance of gestational age at laser surgery in TTTS

Abstract: 0.67 *chi-square testIf deliveries by planned Cesarean section and deliveries following induced labor are excluded, 872 twin pairs remain, where 28.6% were MMP, 44.6% were MFP and 26.8% were FFP. Mean GA at delivery was 246.8 days (SD 20.4) for MMP, 245.5 days (SD 21.8) for MFP and 246.2 days (SD 21.2) for FFP (p>0.05). The distribution of preterm and very preterm births was similar in the three groups. Conclusions: Mean GA at birth does not seem to be correlated to fetal gender in twin pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In our dataset, gestational age at surgery was the main factor influencing the occurrence of CMS. Our findings are in agreement with those of previous studies suggesting a poorer outcome when fetoscopy was performed at an early gestational age, particularly before 18 weeks' gestation. Thus, a higher prevalence of CMS could partially contribute to the poorer outcome of early fetoscopy.…”
Section: Discussionsupporting
confidence: 92%
“…In our dataset, gestational age at surgery was the main factor influencing the occurrence of CMS. Our findings are in agreement with those of previous studies suggesting a poorer outcome when fetoscopy was performed at an early gestational age, particularly before 18 weeks' gestation. Thus, a higher prevalence of CMS could partially contribute to the poorer outcome of early fetoscopy.…”
Section: Discussionsupporting
confidence: 92%
“…10 The relation of Quintero stages with the risk of early IUFD after laser has been evaluated in various studies with inconsistent results. [11][12][13][14] It has been suggested that earlier gestational age (GA), 15 Doppler parameters such as absent or reversed umbilical artery (UA) end-diastolic flow (EDF) in the donor, 9,16,17 and elevated middle cerebral artery peak systolic velocity (MCAPSV) in the recipient 18 are associated with the increased risk of early IUFD.…”
Section: Introductionmentioning
confidence: 99%